Pan-Cancer and Single-Cell Analysis Reveals CENPL as a Cancer Prognosis and Immune Infiltration-Related Biomarker - Feng, Ziyang; Chen, Yu; Cai, Changjing; Tan, Jun; Liu, Ping; Chen, Yihong; Shen, Hong; Zeng, Shan; Han, Ying (Frontiers in Immunology, 2022)
Background: Centromere protein L (CENPL) is an important member of the centromere proteins (CENPs) family. However, the correlation between CENPL expression and cancer development and immune infiltration has rarely been studied. Here, we studied the role of CENPL in pan-cancer and further verified the results in lung adenocarcinoma (LUAD) through in vitro experiments. Methods: The CENPL expression level was studied with Timer 2.0 and Oncomine databases. The potential value of CENPL as diagnostic and prognostic biomarker in pan-cancer was evaluated with TCGA database and GEPIA. The CENPL mutation character was analyzed using the cbioportal database. The LinkedOmics and CancerSEA databases were used to carry out the function analysis of CENPL. The role of CENPL in immune infiltration was studied using TIMER and TISIDB website. Besides, the expression of CENPL was detected through RT-qPCR and western blotting. Immunohistochemistry was used to evaluate the infiltration level of CD8+ T cells. The cell proliferation was detected by EdU and CCK8. Flowcytometer was used to analyze the influence of CENPL in cell cycle and apoptosis. Results: CENPL was increased in most of the cancers. The up-regulation and mutation of CENPL were associated with a poorer prognosis in many cancers. The result showed a significant positive correlation between CENPL and myeloid-derived suppressor cells (MDSCs) infiltration and a negative correlation between CENPL and T cell NK infiltration in most of the cancers. CENPL regulated the cell proliferation and cycle, and was negatively correlated with the inflammation level of LUAD. The in vitro experiments suggested that CENPL was increased in LUAD tissue and cell lines. There was a negative correlation between CENPL expression and CD8+ T cells infiltration. The knock down of CENPL significantly suppressed the expression of CDK2 and CCNE2, and induced G0/G1 arrest and apoptosis of LUAD. Conclusions: CENPL may function as a potential biomarker and oncogene in pan-cancer, especially LUAD. Besides, CENPL was associated with immune cells infiltration in pan-cancer, providing a potential immune therapy target for tumor treatment.